MEDIAÇÕES PEDAGÓGICAS: CONTRIBUIÇÕES AO PLANEJAMENTO DO ENSINO PARA O TRABALHO COM PESSOAS COM DEFICIÊNCIA - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
This research is driven by the question: What are the pedagogical mediations and under what determinations do they take place in the planning of teaching for people with disabilities in public schools? It aims to understand which mediations are or can be carried out to assist in the planning of teaching for people with disabilities in public schools. It also aims to characterize the educational reality of people with disabilities in the municipality of Cândido de Abreu. It seeks to conceptualize pedagogical practices, pedagogical mediation and teaching planning in the inclusion process and to identify the demands of the pedagogical team, teachers and family members regarding the schooling of people with disabilities. As an educational product, to build a guiding document to assist in the pedagogical mediations between those involved in the schooling process of people with disabilities. It is characterized as a qualitative research of an applied nature, because according to Prodanov (2013, p.70) “[...] it aims to generate knowledge for practical application aimed at solving specific problems. It involves local truths and interests.” It begins with the contextualization of the municipality with reference to the municipal notebooks of IPARDES and data collection at the Municipal Department of Education and Culture, starting with a bibliographic review supported by renowned authors to reflect the concepts of inclusion with Heredero (2010) Prietro ( 2005) Mantoan (2003, 2008) Bueno (2008) Pimentel and Souza (2019) Ferreira, Moreira and Volsi (2020), pedagogical mediations , pedagogical practice with Souza (2016) Franco (2016) and Nadal (2016) and teaching planning Veiga (1991) Menezes et al (2016) and Prais, Rosa and Jesus (2018) , still listing the determinants that influence pedagogical practices and their subjects. Finally, it brings details of the fieldwork where it was investigated how the processes of pedagogical mediations and teaching planning occur in a Municipal school that offers Early Childhood Education, Elementary Education I and Special Education. The investigation brought data for the elaboration of the educational product entitled "Guiding document to assist in pedagogical mediations", this one, socialized with the school community, presenting provocations and important points to debate in moments of pedagogical mediations. In view of the results, it is increasingly evident the need for these moments to seek information that assist in the teaching planning process for people with disabilities or disorders, increasingly meeting their specificities and guaranteeing the right to education and consequently effecting the inclusion processes.
Keywords: Mediações Pedagógicas; Planejamento do Ensino; Educação Inclusiva; Aprendizagem; Prática Pedagógica; Pedagogical Mediations; Teaching Planning; Inclusive education; Learning; Pedagogical Practice; CNPQ::CIENCIAS HUMANAS::EDUCACAO